Microteaching to Develop Prospective Biology Teachers' Basic Teaching Skills Following Next Generation Science Standards (NGSS) - Parmin, Parmin; Mohtar, Lilia Ellany; Muhlisin, Ahmad; Trisnowati, Eli; Sukmawati, Ika (Universitas Negeri Semarang, 2024)
Prospective biology teachers have good mastery of the material but are still weak in several indicators of basic teaching skills. Preparing prospective professional biology teachers in Indonesia expects graduates to be able to teach not only in domestic schools but also in schools abroad by integrating Next Generation Science Standards. This study aims to develop prospective teachers' basic teaching skills that integrate Indonesian standards and the Next Generation Science Standards (NGSS) through best practices of microteaching innovation. The research used the Research and Development method. Microteaching lecture tools for prospective biology teachers were developed. The research targets were 82 prospective biology teachers in microteaching courses who were given the same learning environment. The six biology teachers involved came from three partner schools with different statuses: public, nationalist private, and religious private. A t-statistic model comparison test strengthens this finding, where the score of the second microteaching practice differs from the first practice. This research is a form of curriculum implementation for prospective science teachers who integrate NGSS. This research finds that the practice scores in the second microteaching increase after analyzing the first teaching practice video. The impact of these findings provides solutions to create skillful prospective biology teachers.